The impact of realistic simulations with virtual patients in the training of medical students at CESUPA (Research, Society and Development, 2023)
In the context of health education, realistic simulations with virtual patients have been gaining ground in several countries as a new method for students to put their knowledge into practice and develop skills on various topics, simulating situations that could be experienced in practice with the maximum of verisimilitude and ensuring patient safety. The objective of the research is to evaluate the use of virtual simulators in the training of medical students at the Centro Universitário do Estado do Pará (CESUPA), in order to use the results as a basis for improving teaching. As a methodology, a cross-sectional, observational, individual study was used, with a quantitative and qualitative approach. The research involved the participation of 123 medical students who attended realistic simulation activities with virtual patients in the Body Interact™ simulator. A self-administered questionnaire based on the Satisfaction and Self-Confidence in Learning Scale (ESEAA) was used. The participants had higher averages in most of the scale variables, and it was possible to observe that the realistic simulation with virtual patients using the Body Interact™ simulator generated satisfaction and self-confidence among medical students at CESUPA, being an important tool for health education.